Licitaciones de energía eléctrica para el concesionamiento de nuevos generadores en el mercado eléctrico - Guano Zambrano, Galo Ricardo (2015)
In this thesis the evolution of the Ecuadorian electricity sector in relation to the mechanisms of power generation tender to private initiative, demand, concession areas discusses the different types both in procurement markets as national and international negotiations in relation to Europe, North and Latin America. Based on this analysis on these international electricity markets, the advantages and disadvantages results obtained in different market rates applied to each country to serve as a reference to create a standard auction or negotiation by the private sector that can be applied to the Ecuadorian electrical system based on the regulations set by the regulator CONELEC this analysis to the implementation of the new Constitution of the Republic of Ecuador in 2008 the Constituent No15 is contemplated.